Corona protests in Germany: insights into a new movement - Daniel Oppermann (Diálogos Institucionais e Políticas de Enfrentamento da Crise, 2021)
In August 2020, the German capital of Berlin became the stage for political manifestations organized by regional and relatively unknown groups of individuals with diverse political agendas. The German government and the public observed smaller and bigger agglomerations of up to 40.000 citizens of different backgrounds articulating themselves critically towards the political and legal measures taken by the government to address the crisis caused by COVID-19. The public perception of these newly identified networks and organizations and their diverging political agendas posed questions to traditional understandings of political mobilization. While policy makers, researchers, the media and the general public are often categorizing political groups or movements into specific sections including left, right, center and others, the newly growing so called “anti-corona” or “corona-sceptical” movement in Germany did not allow an easy categorization at first sight. This chapter will give an overview and a first insight into this newly evolving movement, its political agenda and into its mechanisms of political mobilization. It will be shown, how a heterogeneous mixture of middle class citizens, peace movement activists, right wing extremists, antisemitic conspiracy theorists and others joined a common platform strengthened by social media activism and so called alternative media channels.
Keywords: 330; COVID19; Germany; political mobilization; social media